Bean rust resistance strategy at CIAT - Schwartz, Howard F.; Temple, Steven R. (1978)
Data obtained from the international Bean Rust Nursery (IBRN) in 1975-76 showed that none of the 132 cv. and breeding lines tested was resistant to bean rust; however, some were susceptible only in specific geographical regions. CIATs bean program has concentrated its efforts on selecting rust-resistant cv. from crosses from IBRN parents under natural and artificially induced field conditions. It identifies unique and more stable forms of rust resistance by specific and/or horizontal mechanisms, but emphasis is placed on resistance mechanisms easy to select in Large segregating populations. (CIAT)